EPA and DHA Status of South Asian and White Canadians Living in the National Capital Region of Canada. Issue 10 (23rd August 2014) - Nagasaka, Reiko; Gagnon, Claude; Swist, Eleonora; Rondeau, Isabelle; Massarelli, Isabelle; Cheung, Winnie; Ratnayake, Walisundera M. N.
Abstract: To minimize the risk of cardiovascular disease (CVD), most dietary guidelines have recommended consuming 500 mg/day of eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA) or two servings of oily fish/week. The sum of percent EPA and DHA in red blood cell (RBC) total fatty acids‐termed the omega‐3 index‐has been proposed as a biomarker for assessing the risk of death from CVD. The omega‐3 indices of ≤4, >4 to <8 and ≥8 % have been proposed to be associated with high, intermediate and low CVD risks, respectively. In this study, we determined the EPA + DHA intake level and the omega‐3 index of South Asian Canadians (SAC; n = 308) and white Canadians (WC; n = 341) age 20–79 years living in the National Capital Region of Canada. The mean EPA + DHA intake levels were 569 ± 571 mg/day for SAC and 684 ± 865 mg/day for WC and 46 % of SAC and 43 % of WC met the recommended EPA + DHA intake level of 500 mg/day. The mean omega‐3 indices were 6.6 and 5.9 % for SAC and WC respectively. The suggested cardio‐protective target level for the omega‐3 index of ≥8 % was observed only in 19.8 % of SAC and in 9.4 % of WC subjects. The majority of the participants (74.4 % of SAC and 82.7 % of WC) were in the >4 to <8 % range. These results suggest that although study participants' dietary intake of EPA + DHA is adequate, this intake was not sufficient to provide an omega‐3 index that is considered cardio‐protective.